GOOD CORPORATE GOVERNANCE MANAGEMENT ON CORPORATE VALUES (Empirical Study on Chemical Companies listed on the Indonesia Stock Exchange Period 2013-2015) - Budiyono Budiyono; Fitriah Ayu Wulansari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
The purpose of this study was to examine the effect of good corporate governance on company value. Proxy of good corporate governance, namely the composition of the board of commissioners, institutional ownership, managerial ownership. The research samples are chemical companies listed on the Stock Exchange in 2013-2015. The purposive sampling method was used in the selection of samples in order to obtain a sample of 10 chemical companies with a total observation of 30 observation data for 3 years. The data analysis techniques using multiple regression analysis. Company value is measured using Tobin’s Q. Based on the results of testing the hypothesis, the results show that only the composition of the board of directors variables has a negative effect on the value of the company while the other two independent variables have a positive effect on the value of the company.